Meeting With S.C & S.T Parliamentarians in the Context of the Formulation of the Ninth Five Year Plan (1997-2002) - Planning Commission (Planning Commission, 1996)
To address the special problems and needs of SC/ST Communities, the Government has adopted a three-pronged strategy which includes special measures for - i) Social Empowerment through Educational Development; (ii) Economic empowerment through Poverty Alleviation and Employment and Income Generation; and iii) Social Justice through Legislative Support and Other Programmes. These special measures which are put into action through the nodal Ministry of Welfare and other line Ministries are expected to play a supplementary-cum complementary role to the other general development programmes and be able to meet the special needs of these Groups.
Planning Commission Government of India
Planning Commission Government of India